(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2018)
The aim of the article is to determine Koszalin competitive position according to other selected towns (Grudziądz, Włocławek, Gdynia, Słupsk, Sopot, Elbląg, Kalisz, Konin, Leszno i Świnoujście. The competitive position was set for 2010 and 2015, using synthetic indicators. The data comes from the Central Statistical Office – Local Data Bank. Based on the analyzes carried out, it was found that Koszalin occupies a high competitive position in relation to analyzed towns. In addition, Koszalin has a chance of further development in the future as it has high endogenous potential.